Oncologists' Perspective on Dental Care Around the Treatment of Head and Neck Cancer: A Pattern of Practice Survey. Issue 1 (January 2022) - Ward, Matthew C.; Carpenter, Michael D.; Noll, Jenene; Carrizosa, Daniel; Moeller, Benjamin J.; Helgeson, Erika S.; Lalla, Rajesh V.; Brennan, Michael T.
Abstract : PURPOSE: Patients with head and neck cancer are at risk of long-term dental complications. Proper dental assessment pre- and post-treatment can improve outcomes but is logistically challenging. We surveyed oncologists to better understand their perspectives surrounding dental care in this unique population. METHODS: We surveyed oncologists at institutions associated with an ongoing national study of oral health after treatment of head and neck cancer. Seventeen questions were used to assess provider characteristics, patterns of practice, patterns of referral, barriers to referral, and willingness to apply fluoride varnish in the oncology clinic. RESULTS: Ninety-seven oncologists were invited from six institutions, of whom 40 (41%) responded. Surgeons represented 45% of the sample, followed by radiation oncologists (40%) and medical oncologists (15%). Both generalists and subspecialists were included. All practiced in a metropolitan area with an academic dental practice, and many felt that this improved access to care. Despite this, most oncologists thought that financial factors were a significant barrier to obtaining timely dental care. Most oncologists performed a dental assessment during visits. Oncologists felt qualified to identify the most significant complications of treatment, such as exposed bone, but felt underqualified to identify early changes in need of intervention. When asked if the oncology clinic could apply fluoride varnish during follow-ups, most stated that this seemed feasible but would require education and financial support. CONCLUSION: Oncologists often perform limited dental evaluations during their routine visits. Given the challenges associated with access to proper dental care for this population, these oncology visits may provide a window for preventative intervention.